The Secret Portrait of a Romantic? On the Recent Biographies of Karel Jaromír Erben - Gawarecka, Anna (Poznańskie Studia Slawistyczne, 2023)
In 1853, Karel Jaromír Erben published a collection of ballads Kytice, which was immediately seen as a model of national literature. The contact of this model with Romanticism is only selective, because it does not consider all the metaphysical dilemmas resulting from the appreciation of the individualistic attitude to the world. It might seem that Kytice should share the fate of other 19th century texts of culture which are currently attributed the position of a respectable, old fashioned literary monument. Meanwhile, in recent years, two novels have been published directly drawing inspiration and thematic material from the life of the poet, namely: Vřeteno osudu. Tajná zpověď by Karel Jaromír Erben by Otomar Dvořák (2015) and Stará škola by Petr K. Procházka (2022). Both literary biographies expose the close, though hidden, connections between Erben’s poetics and worldview with the Romantic aesthetic and ideological context.